Piper yellow mottle virus : A deep dive into the genome - Chung, Hung Hui; Leonard Whye Kit, Lim; Jia Xin, Liew (Elsevier Inc., 2022)
The piper yellow mottle virus (PYMoV) is a member under the genus Badnavirus and family Caulimoviridae. This virus has been causing nuisance and massive yield loss to the black pepper farming industry globally as it causes the stunt disease. In this study, we venture into the unattempted genome comparison across different isolates from different countries to look into the country-specific divergence. As a result, the genome comparison unraveled that the GC contents of the genomes isolated from host species Piper nigrum are comparatively lower in contrast to that isolated from other species. The genome fragment lengths of ORF2 and ORF4 tend to show country-specific patterns. The haplotype analysis further disclosed on the country-specific SNPs necessary for marker development. The whole genome phylogenetic tree constructed provides higher resolution in distinguishing country-specific clusters, in contrast to reverse transcriptase gene tree alone. The reverse transcriptase protein modelling further reinforced our apprehension on the regulators of these country-specific divergences. It is suggested that more PYMoV genomes to be sequenced from other countries to deepen our understanding on the virulence and variations of this virus in order to prevent massive harvest loss in the future.